Investigation of the structural–phase state of ultrafine plasmochemical ZrO2 (Y) powders; IOP Conference Series: Materials Science and Engineering; Vol. 66: 20th International Conference for Students and Young Scientists: Modern Techniques and Technologies (MTT'2014), Tomsk, Russia, 14-18 April 2014 - Gyngazov (Ghyngazov) S. A. Sergey Anatolievich; Vasiljev I. P. Ivan Petrovich; Frangulyan (Franguljyan) Т. S. Tamara Semenovna; Khaidukova V. M.; Mylnikova T. S. Tatyana Stepanovna (2014, 2014)
Title screen